LENSED MULTIPLE BAND MULTIPLE BEAM MULTIPLE COLUMN DUAL-POLARIZED ANTENNA (2021)
The inventive subject matter provides apparatus, systems and methods in which a high port count base station antenna uses an array of spherical lenses with multiple ports per frequency band, containing multiple frequency bands, and capable of multiple beam operation. In a preferred embodiment, the antenna system comprises a plurality of spherical, dielectric lenses, stacked vertically, where each lens is surrounded by four or more lower frequency radiating elements, or one circular element. The circular element can have multiple sub-elements, along with feed gaps.